Tribological properties of Mo and CaF2 added SiC matrix composites at elevated temperatures. (July 2017) - Li, Fei; Zhu, Shengyu; Cheng, Jun; Qiao, Zhuhui; Yang, Jun
Abstract: SiC matrix high temperature solid-lubricating composites with addition of different contents of CaF2 and Mo were fabricated by hot pressed sintering, and their tribological behavior was investigated over a broad temperature range between room temperature to 1000 °C. It was found SiC matrix composite with addition of 20 vol% Mo and 30 vol% CaF2 to exhibit excellent solid lubricity and wear resistance. Especially at 1000 °C, it has the lowest friction coefficient of 0.17 and a favorable wear rate of 4.08×10 −6 mm 3 /N m. The low friction and wear mechanisms were discussed in detail. Highlights: The SiC matrix solid-lubricating composites are prepared. Synergism of Mo and CaF2 contributed to the lubrication of SiC at high temperature. SiC matrix composites provided favorable lubricating properties at 800 and 1000 °C. 50 vol%SiC-20 vol%Mo-30 vol%CaF2 showed the best lubricating properties at 1000 °C.